Effects of Sulforaphene on the Cariogenic Properties of Streptococcus Mutans In Vitro and Dental Caries Development In Vivo - Yuehong Zhou; Binhan Zhang; Yufei Wang; Rongdang Hu (MDPI AG, 2023)
Sulforaphene (SFE) is a common nutritional supplement with antibacterial, anti-cancer, and anti-inflammatory effects. However, the effects of SFE on the cariogenicity of Streptococcus mutans and dental caries have not been reported. The objectives of this study were to investigate the caries-controlling potential of SFE. The effects of SFE on S. mutans were investigated using the broth microdilution method, crystal violet staining, SEM observation, acid tolerance assays, lactic acid quantification, and polysaccharide measurements. A rat caries model was established to evaluate the caries-controlling effects and biocompatibility of SFE in vivo. SFE inhibited S. mutans growth and biofilm formation. Furthermore, SFE restrained the cariogenic properties of S. mutans, including its acid production, acid tolerance, and extracellular polysaccharide production, without affecting the bacterial viability at sub-inhibitory levels. In the rat caries model, SFE significantly arrested the onset and development of dental caries. Moreover, no visible hemolytic phenomenon or cytotoxicity was detected in the SFE groups. After four weeks of SFE treatment, all rats remained in apparent good health with no significant differences in weight gain; their hemogram and biochemical parameters were normal; no pathological changes were observed in the oral mucosa, liver, or kidneys. In conclusion, SFE was safe and inhibited the development of caries effectively.